Origin of α-mannosidase activity in CSF. (June 2017) - Tasegian, Anna; Paciotti, Silvia; Ceccarini, Maria Rachele; Codini, Michela; Moors, Tim; Chiasserini, Davide; Albi, Elisabetta; Winchester, Bryan; van de Berg, Wilma D.J.; Parnetti, Lucilla; Beccari, Tommaso
Abstract: The α-mannosidase activity in human frontal gyrus, cerebrospinal fluid and plasma has been analyzed by DEAE-cellulose chromatography to investigate the origin of the α-mannosidase activity in cerebrospinal fluid (CSF). The profile of α-mannosidase isoenzymes obtained in CSF was similar to that in the frontal gyrus but different from that in human plasma. In particular the two characteristic peaks of lysosomal α-mannosidase, A and B, which have a pH-optimum of 4.5 and are found in human tissues, were present in both the frontal gyrus and CSF. In contrast the majority of α-mannosidase activity in human plasma was due to the so called intermediate form, which has a pH-optimum of 5.5. The results suggest that the intermediate form of α-mannosidase in plasma does not cross the blood–brain barrier and that the α-mannosidase activity present in the cerebrospinal fluid is of lysosomal type and of brain origin. Thus the α-mannosidase activity in cerebrospinal fluid might mirror the brain pathological changes linked to neurodegenerative disorders such as Parkinson's disease.